Le refus de « parler chrétien » : dissidence d’un motif à travers La Farce de Maître Pathelin, Pantagruel et le Cymbalum mundi - Mathilde Bernard (Les Dossiers du GRIHL)
La Farce de maître Pathelin, Pantagruel and the Cymbalum mundi each involve a character whose distinctive feature is that he communicates so as not to make himself understood, when he is perfectly able to make himself understood to the people he is addressing. Pathelin and Panurge speak in tongues and the dogs from the Cymbalum mundi bark whereas they can speak. This article investigates the workings and motivations of this refusal to « speak Christian », through three works from the end of the Middle Ages and the beginning of the Renaissance in which the value of language as human glory and foundation of society is questioned.